KEBIJAKAN KRIMINAL TERHADAP PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG MENURUT UNDANG-UNDANG NO. 8 TAHUN 2010 - Risna Oktaviyanti Utami; Bismar Nasution; Muhammad Hamdan; Marlina Marlina (Universitas Sumatera Utara, 2017)
ABSTRACT Money laundering as a form of crime that not only threatens the stability of the economy and the integrity of the financial system, but also can harm the joints of the life of society, nation and state. Impact of globalization on the development of crime. One factor is the crime can flourish because of the encouragement of technology. The rapid development of science and technologies have an impact on the complexity of the crime of money laundering, it is impossible not money laundering also utilize technological means. The impact was so great from the money laundering led to a State should establish a policy on the prevention of crime and money laundering. Therefore this study focuses on the issue of criminal policy, policy formulation as well as efforts to prevent and combat money laundering. The survey results revealed, through the criminal penal policy that is based on Law No. 8 of 2010 is a form in which the criminalization of money laundering must be prevented and eradicated. Criminal policy in the fight against crime can not be separated from policy formulation. Policy formulation is the first step in crime prevention that functionally can be seen as part of the planning and crime prevention mechanism as outlined into the legislation. In Law No. 8/2010 specifically authorizes the Financial Transaction Analysis Reporting Centre (INTRAC) in an effort preventing and combating money laundering and cooperation that made the international world. Keywords: Criminal Policy, Policy Formulation, Money Laundering